2021
DOI: 10.1021/acsami.1c02237
|View full text |Cite
|
Sign up to set email alerts
|

Humidity Sustainable Hydrophobic Poly(vinylidene fluoride)-Carbon Nanotubes Foam Based Piezoelectric Nanogenerator

Abstract: Light weight lead free, polymer, and carbon nanotubes based flexible piezoelectric nanogenerators have prompted widespread concern for harvesting mechanical energy and powering next generation electronics devices. Herein, lightweight polyvinylidene fluoride (PVDF)-carbon nanotube (CNT) foam was prepared to fabricate humid resistant hydrophobic flexible piezoelectric nanogenerator to converts mechanical energy into electricity for the first time. Hydrophobic piezoelectric PVDF-CNT foam with density of 0.15 g/cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…Moreover, it was assumed that similar to the phenomenon of a capacitor, charge-pumped electron flow was driven back and forth via an external load, whereby the charging and discharging process create an alternating currenttype charge signal. [52][53][54][55] In 2D MoS 2 materials, the piezoelectric screening effect caused by crystalline point defects, such as sulphur vacancies (which act as free charge carriers), plays a significant role in screening the strain-induced piezoelectric polarisation charges and hence the piezoelectric performance decreases. 56,57 It was also reported that such a piezoelectric screening effect under the mechanical deformation of piezoelectric nanosheets also occurs due to the presence of thermally existing free charge carriers, which cancel the piezoelectric-developed electric charges and consequently the piezoelectric output voltage/ current of the nanogenerator is reduced.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it was assumed that similar to the phenomenon of a capacitor, charge-pumped electron flow was driven back and forth via an external load, whereby the charging and discharging process create an alternating currenttype charge signal. [52][53][54][55] In 2D MoS 2 materials, the piezoelectric screening effect caused by crystalline point defects, such as sulphur vacancies (which act as free charge carriers), plays a significant role in screening the strain-induced piezoelectric polarisation charges and hence the piezoelectric performance decreases. 56,57 It was also reported that such a piezoelectric screening effect under the mechanical deformation of piezoelectric nanosheets also occurs due to the presence of thermally existing free charge carriers, which cancel the piezoelectric-developed electric charges and consequently the piezoelectric output voltage/ current of the nanogenerator is reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was assumed that similar to the phenomenon of a capacitor, charge-pumped electron flow was driven back and forth via an external load, whereby the charging and discharging process create an alternating current-type charge signal. 52–55…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have taken a variety of approaches to increase dielectric constant and decrease dielectric loss in order to obtain nanocomposites with excellent dielectric properties and develop high performance piezoelectric nanogenerators (PNGs). To endow polymer nanocomposites with high dielectric constant, researchers have homogeneously dispersed ferroelectric ceramic particles or fibers with high dielectric constant [19][20][21][22][23] and/or incorporated conductive fillers such as metal particles, carbon-based materials, and semiconductor, into the polymer matrix [24][25][26][27][28][29][30]. Among various ceramic materials including PbZr 1−x Ti x O 3 (PZT), PZT:La (PLZT), PbTiO 3 (PT), and Pb(Mg 1/3 Nb 2/3 )O 3 (PMN), lead-free barium titanate (BaTiO 3 ) is the most environmentally friendly of the ceramic materials, and it also has high piezoelectric and ferroelectric characteristics, as well as a high dielectric constant [19,23].…”
Section: Introductionmentioning
confidence: 99%
“…5 Among these NPs, CNTs/ MWCNTs are interesting materials due to their 1D structure and high thermal and electrical conductivity. Also, the incorporation of CNTs/MWCNTs into the PVDF matrix can improve the electroactive b-phase, and inherently it will enhance the EMI shielding, 6 dielectric, 7 piezoelectric, 8 ferroelectric, 9 triboelectric, 10 and thermal properties 11 of the PVDF nanocomposite. Kim et al 12 blended PVDF with MWCNTs and observed that an almost pure b-phase was obtained when the weight percentage of MWCNTs was less than 0.2 wt%.…”
Section: Introductionmentioning
confidence: 99%